The contribution of mosses to the carbon and water exchange of arctic ecosystems: quantification and relationships with system properties. - Douma, J.C.; van Wijk, M.T.; Lang, S.I.; Shaver, G.R. (Plant, Cell & Environment, 2007)
Water vapour and CO